SILABUS AS A MEANS OF IMPROVING THE QUALITY OF PROFESSIONAL TRAINING OF STUDENTS IN INSTITUTIONS OF HIGHER BUILDING EDUCATION - Petrunok , Tetiana; Blagodarenko , Ludmila (Physical and Mathematical Education, 2022)
Problem formulation. The article examines the problem of creating a new type of educational and methodological support, the use of which is inextricably linked with the introduction of modern educational models of learning. It is emphasized that the multi-vector training of students of construction specialties requires successful formation of competencies in various disciplines of both general and professional cycles of training, so there is a problem of determining the content of syllabus as a means of improving the quality of professional training in higher education Materials and methods. The study is based on the analysis of: scientific developments of domestic scientists, systematized and summarized the results of pedagogical observation of the educational process in institutions of higher construction education; standard of higher education in Ukraine in this field and for a particular specialty, taking into account the levels of higher education (bachelor’s or master’s degree), legislative and regulatory documents used to ensure the quality of education. Results. The content of the concept of syllabus as a means of improving the quality of professional training is determined. It is substantiated that the syllabus is a curriculum of the discipline, which allows individualizing and differentiating the educational process, as well as providing each student with opportunities to build stages of their own learning activities and manage these stages in their dynamics. It is specified that the syllabus is created in accordance with the standard of higher education of Ukraine in this field and for a certain specialty, taking into account the educational degree (bachelor or master). It is shown that the structure of the syllabus is based on general didactic principles, and its creation must take into account current trends in the construction industry, the characteristics of types and objects of professional activity. Conclusions. It is substantiated that the simulation of the syllabus is multifaceted and involves the achievement of basic educational goals. It is stated that the main conceptual aspect of the introduction of syllabus is based on the unity of consciousness and activity, which allows not only to provide knowledge of a particular discipline, but also to form a person prepared for professional activities. It is shown that the main purpose of the syllabus is to regulate the educational process, ensure flexibility and adaptability of learning models.